ChemInform Abstract: Constituents of the Stem Barks of Ailanthus altissima and Their Potential to Inhibit LPS‐Induced Nitric Oxide Production. Issue 27 (18th June 2015) - Kim, Hye Mi; Kim, Su Jung; Kim, Ha‐Yeong; Ryu, Byeol; Kwak, Hokwang; Hur, Jonghyun; Choi, Jung‐Hye; Jang, Dae Sik
Abstract Fifteen compounds, including three new canthin‐6‐one‐glycosides (I), are isolated and evaluated for their inhibitory effects on LPS‐induced nitric oxide (NO) production in RAW 264.7 cells at non‐toxic concentrations.